Investment Need Plans Analysis Using ICOR Method in Kuningan Regency as Metropolitan Cirebon Raya - Neni Nurhayati; Dadang Suhendar (Indonesian Journal Of Business And Economics, 2018)
This paper aimed at answering the goal of establishing Cirebon Raya Metropolitan as a center for economic development. Accelerated development is needed to increase economic growth in Kuningan Regency as one of the Greater Cirebon Metropolitan Area by increasing investment realization. Because one of the determinants of economic growth is investment, an analysis of the investment needs plan and data on investment sectors that are potential to be developed in Kuningan District are needed. Through this research, accurate data is obtained about the condition and development of investment in Kuningan Regency.To achieve this goal, an analytical description research method was conducted with data sources in the form of primary data and secondary data sourced from DPMTPSP, Bappeda, and BPS in Kuningan Regency related to Sectoral GRDP and investment data in both Kuningan and West Java Provinces. The data analysis technique uses the Incremental Capital Output Ratio (ICOR) method. This study lasted for 1 (one) year. The results of the study show that in welcoming the Greater Cirebon Metropolitan, the investment in the base sector in Kuningan Regency must be focused on the development of the Education Services, Transportation and Warehousing sector, and the agricultural and tourism products processing industries based on Agriculture, and natural resource potential.